KOMPLEKSITAS BUDAYA POLITIK AKAR RUMPUT DAN PROSPEK DEMOKRASI LOKAL DI INDONESIA (Studi Kasus di Desa Sunyalangu, Kabupaten Banyumas, Jawa Tengah) - Khairu Roojiqien Sobandi; Adhi Iman Sulaiman (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
The concept of democracy in Indonesia actually has already exists at the grassroots level, which is in the village, and thus, to create democracy should be from the bottom. At this level, we would know how to create, strengthening, and consolidating democracy in regional even in national level. Hence, the core institution for democratization is the Village at the grassroots level. This case study research conducted in Sunyalangu Village, Central Java, Indonesia that is include to a poor village in Banyumas region and thus, it become a marginal village. I examine their political cultures on national general elections from 1971 to 2004 and the relationships between village’s executive and legislative roles on the lowest level of democratization. This focus shows how empirical democracy created. The result of this research shows that their political cultures is inconsistence in elects their political parties and representatives because of personal needs and their moral economy to the political party. Moreover, the village government (local executive) is still dominates the relationship with local parliament (BPD) because of the institutional and geographical constraints at the grassroots level. The implication of this situation is to re-think the concept of democracy in grassroots level by creating the democracy culture.